Analisis Naratif Vladimir Propp dalam Film “Lafran” Karya Faozan Rizal - Waldi Afala Sinaga; Andini Nurbahri (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study explores the representation of Islamic leadership values embodied by Lafran Pane in the film Lafran, directed by Faozan Rizal, using Vladimir Propp’s narrative analysis framework. The film was selected for its portrayal of a historical Muslim figure who inspires students, yet remains underexplored academically, especially in terms of narrative structure. Employing a qualitative approach, the research identifies narrative functions such as absentation, villainy, helpers, and recognition that shape Lafran’s transformation into a principled leader. The findings reveal that Lafran Pane is depicted as an individual with strong ideas, spiritual integrity, and moral courage. Values such as justice, trustworthiness (amanah), consultation (shura), and wisdom are conveyed through dialogue, visuals, and plot progression. These values align with Islamic character education and are reinforced through the trials and triumphs presented in the film. The study concludes that biographical films hold great potential as tools for da’wah and leadership education. The narrative of Lafran Pane offers both a mirror and motivation for Muslim students to uphold their values, pursue truth, and serve society with integrity.